Molecular analysis of aniridia patients for deletions involving the Wilms' tumor gene - Drechsler, Matthias; Meijers-Heijboer, E. J.; Schneider, S.; Schurich, Bärbel; Grond-Ginsbach, Caspar; Tariverdian, Gholamali; Kantner, G.; Blankenagel, Anita; Kaps, D.; Schroeder-Kurth, Traute; Royer-Pokora, Brigitte (Human genetics, 1994)
A human aniridia candidate (AN) gene on chromosome 11p13 has been cloned and characterized. The AN gene is the second cloned gene of the contiguous genes syndrome WAGR (Wilms' tumor, aniridia, genitourinary malformations, mental retardation) on chromosome 11p13, WT1 being the first gene cloned. Knowledge about the position of the AN and WT1 genes on the map of 11p13 makes the risk assessment for Wilms' tumor development in AN patients possible. In this study, we analyzed familial and sporadic aniridia patients for deletions in 11p13 by cytogenetic analyses, in situ hybridization, and pulsed field gel electrophoresis (PFGE). Cytogenetically visible deletions were found in 3/11 sporadic AN cases and in one AN/WT patient, and submicroscopic deletions were identified in two sporadic AN/WT patients and in 1/9 AN families. The exact extent of the deletions was determined with PFGE and, as a result, we could delineate the risk for Wilms' tumor development. Future analyses of specific deletion endpoints in individual AN cases with the 11p13 deletion should result in a more precise risk assessment for these patients.
Gesehen am 18.04.2024